2010
DOI: 10.1002/cmmi.420
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐small gadolinium oxide nanoparticles to image brain cancer cells in vivo with MRI

Abstract: The majority of contrast agents used in magnetic resonance imaging (MRI) is based on the rare-earth element gadolinium. Gadolinium-based nanoparticles could find promising applications in pre-clinical diagnostic procedures of certain types of cancer, such as glioblastoma multiforme. This is one of the most malignant, lethal and poorly accessible forms of cancer. Recent advances in colloidal nanocrystal synthesis have led to the development of ultra-small crystals of gadolinium oxide (US-Gd(2)O(3), 2-3 nm diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 49 publications
9
97
0
Order By: Relevance
“…Gadolinium oxide, one of the rare earth oxides, is used as an additive in other ceramics, e.g., Gd 2 O 3 was used to stabilize the tetragonal phase of zirconia [5] and to improve the densification of sintered SiC [6]. At present, attempts are being made to use strongly paramagnetic Gd 2 O 3 nanoparticles for contrast enhancement in magnetic resonance imaging (MRI) [7] and, most recently, Faucher et al [8] reported on the possibility of using ultra-small gadolinium oxide nanoparticles to image brain cancer cells in vivo by MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Gadolinium oxide, one of the rare earth oxides, is used as an additive in other ceramics, e.g., Gd 2 O 3 was used to stabilize the tetragonal phase of zirconia [5] and to improve the densification of sintered SiC [6]. At present, attempts are being made to use strongly paramagnetic Gd 2 O 3 nanoparticles for contrast enhancement in magnetic resonance imaging (MRI) [7] and, most recently, Faucher et al [8] reported on the possibility of using ultra-small gadolinium oxide nanoparticles to image brain cancer cells in vivo by MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Although the cells, especially Ba/F3, only partly took up the particles, they still were exposed to the Gd extracellularly, as the nanoparticles were not washed away during these observations. Taking this into account, the viability was not significantly reduced and this preserved good viability is confirmed by Faucher et al 22 It is very promising that Ba/F3 cells withstand the Gd and DEG exposure to the same extent as THP-1 (previously studied in Klasson et al 15 However, toxicology investigations of the Gd 2 O 3 nanoparticles need more thorough viability studies and long term biological effects need to be evaluated. In addition, it has to be remembered that before considering …”
Section: Viability and Solubility Uptakementioning
confidence: 63%
“…However, it was shown in aqueous media that these nanoparticles tend to agglomerate with subsequent decrease in the relaxivity [175]. nonetheless, improved contrast was obtained in the visualization of brain tumors [176] or in the detection of glioblastoma cancer cells in vivo [177]. These particles can furthermore be modified on their surface by incorporation of various functional groups such as organic acids [178] or peG [179], suggesting potential control over stability and biodistribution.…”
Section: Gadolinium Oxide Nanoparticlesmentioning
confidence: 99%